WACANA “SANGKAN-PARAN” DALAM KAKAWIN AJI PALAYON: SEBUAH ANALISIS SEMIOTIK - Suarka, I Nyoman (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2009)
Abstract Kakawin Aji Palayon represents kakawin which combines the concept of religion and beauty. The various levels of sign system in Kakawin Aji Palayon either in the form of verbal or nonverbal, need to have various level of reading. By following the primary reading level of soul (Atma) on the way to its origin which is called Paramatma to amalgamate with God, so it can be said that “sangkan paran” discourse in Kakawin Aji Palayon means that every existence will be ended with its disappearance. The existence will be ended in death (palayon).Everything will achieve its goal (paran) and return to its origin (sangkan). Microcosm or body (mikrokosmos) will pass away and back to the macrocosm or nature (makrokosmos). Although the soul (Atma) will not die, but soul (Atma) also will return and get together with its origin which is known as Paramatma.